Associations between sleep bruxism and primary headaches: a descriptive study. - Conti Réus, Jéssica; Duarte, Joyce; Pauletto, Patrícia; Polmann, Helena; de Queiroz, Luiz Paulo; Silva Maia, Israel; De Luca Canto, Graziela (Journal of Oral & Facial Pain & Headache, 2024)
To evaluate the association between definitive sleep bruxism and primary headaches and to analyze other variables that may also be associated with definitive sleep bruxism. A descriptive study was carried out with a sample of adults with a medical indication for polysomnography in Florianópolis, Brazil. Data were collected in three phases: questionnaires, physical examinations and polysomnography. Pearson's chi-square test and unadjusted and adjusted binary regressions were carried out using the Statistical Package for the Social Sciences computer program. The significance level was 5%, and the confidence interval (CI) was 95%. The test power was calculated by the G*Power computer program. The sample consisted of 23 men and 19 women, with an average age of 45.6 ± 15 years. Approximately 76% of the participants had sleep bruxism, and 57% had primary headache. The odds ratio between definitive sleep bruxism and primary headaches was 0.86 (95% CI 0.20 to 3.64; p = 0.71), demonstrating no association between these variables. Among the other variables analyzed, only alcohol consumption was associated with bruxism, with an odds ratio of 5.96 (95% CI 1.26 to 28.28; p = 0.03). According to binary regression, no variable was a confounding factor for definitive sleep bruxism. The power of the test was 0.028. There was no association between definitive sleep bruxism and primary headaches. Alcohol consumption increases the patient's chance of having sleep bruxism by almost six times. Knowledge about the association of sleep bruxism with other variables can help dentists detect it and explain the condition to patients.